A tecnologia do ozônio associada à embalagem em atmosfera modificada como alternativa ao uso do cloro no aumento da vida de prateleira do camarão branco (litopenaeus vannamei) inteiro resfriado - Santos, Tanyla Cybelly Lira (Universidade Federal Rural do Semi-Árido, 2017)
The objective of the present study was to evaluate the combined use of ozone technology with modified atmosphere packaging as an alternative to ensure the microbiological safety, quality and shelf life of whole chilled Pacific white shrimp (Litopenaeus vannamei). Shrimp samples were immersed in ozonated water (1 ppm, 10 min) in chlorinated water (5ppm, 10 min), and as control group, shrimp with no treatment was used. After immersion, shrimp samples were drained, and packed in atmospheric air (Control) and modified atmosphere (100% CO2). All samples were stored under refrigeration (4±1°C) for 12 days. Shrimp samples were with drawn every 3 days for microbiological (Salmonella spp, Staphylococcus aureus, total mesophilic and psychrotrophic counts), sensory (Quality index method - MIQ) and physicochemical (pH, total volatile bases nitrogen (TVB-N), Trimethylamine nitrogen (TMA-N) and the measurement of thiobarbituric acid reactive substances (TBARS)) analyzes. The results were statistically evaluated using Univariate Variance Analysis (ANOVA). The Tukey test was used to examine the individual statistical differences between treatments, at a significance level of 0.05.Linear regressions were made to predict the shrimp shelf life. The pre-treatment of the shrimp samples with ozonated water, followed by packaging in modified atmosphere (100% CO2) and storing at refrigeration temperature (4ºC), demonstrated efficacy in increasing the estimated shelf life (24 days), when compared to control group (9 days) and pre-treatment with chlorinated water (11 days). During this period, the sensorial characteristics of pre-treated group with ozone remained acceptable, the melanosis index remained low, the total count of mesophilic and psychrotrophic bacteria remained low, pH, N-BVT, N-TMA and TBARS remained low and constant, when compared to the other treatments. Thus, it can be concluded from these results that the combined effect of ozone and modified atmosphere ensured the physic-chemical and microbiological quality and extended the shelf life of white shrimp (L. vannamei) stored at 4 ° C
Ozone technology associated with modified atmosphere package in order to increase the shelf life of chilled while shrimp (litopenaeus vannamei)
Keywords: Crustáceo; Qualidade; Segurança alimentar; Tecnologia de barreiras; Crustacean; Quality; Safety food; Barrier technology; CIENCIAS AGRARIAS::MEDICINA VETERINARIA